2022
DOI: 10.1007/s13300-022-01287-z
|View full text |Cite
|
Sign up to set email alerts
|

IDegLira for the Real-World Treatment of Type 2 Diabetes in Italy: Protocol and Interim Results from the REX Observational Study

Abstract: Introduction IDegLira was shown to maintain glycemic control while reducing risk of hypoglycemia and body weight gain. The REX study was designed to generate real-world evidence on the use of IDegLira in Italian clinical practice in two different subgroups of patients, those switching to IDegLira from a basal insulin-supported oral therapy (BOT group) and those from a basal plus bolus insulin regimen (BB group). Methods Adult patients with T2D diagnosed for at least 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…30 Furthermore, IDegLira has recently emerged as a valid and simple alternative to a complex BB insulin regimen for patients with T2D and poorly controlled diabetes, as documented by very high HbA1c (9%-15%). 31 The extent of HbA1c reductions in both groups of patients was consistent with that obtained in other Italian observational studies 21,22 and similar to that reported in the European retrospective study, 25 but also with the results of the randomized controlled trials of the DUAL programme. [7][8][9][10][11][12] In DUAL-V, patients on basal-only insulin randomized to IDegLira had a greater HbA1c reduction of 0.6% than those randomized to continuing and uptitrating basal insulin.…”
Section: Discussionsupporting
confidence: 89%
“…The baseline clinical characteristics of the study population were previously discussed in the interim results paper. 25 As expected, patients in the BB group were in a more advanced and complicated disease stage compared with those in the basal only group and had an average lower mean HbA1c but were still far from T A B L E 2 Patients with HbA1c <7% during the observation period in the overall population of evaluable patients and by patient groups. the target value of 7%.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This included the incidence of hypoglycemia which is more specifically expected to be lowered by switching from MDI to IDegLira. The ongoing prospective real-life studies, such as the Italian multicenter REX study [ 24 ], will probably provide more relevant observations on this important issue. Finally, the growing use of weekly GLP-1RAs, due to reduced frequency of administration and to increased potency in terms of glycemic and weight control, could call into question the relevance of our data for current clinical practice.…”
Section: Discussionmentioning
confidence: 99%